Corporate governance: A Philippine perspective - Caoile, Patrick V. (Animo Repository, 2014)
Corporate Governance refers to a system whereby share holders, creditors, and other stakeholders of a corporation ensure that management enhances the value of the corporation as it competes in an increasingly global market place (SEC Memo No. 2) Corporate governance establishes the need to comply with statutory requirements. There is also a need to establish other factors aside from financials to ascertain compliance and enhancing the value of the corporation. This research process to use the balanced score card to allow a more holistic approach to corporate governance of individual companies.